Unveiling The Impact of Perceived Control, Hedonic and Utilitarian Values on Skincare Purchase Intent: Emotional Pleasure as A Mediator, Flow Experience As A Moderator For The Skintific Brand - Yokie Radnan Kristiyono; Avi Nurul Afia (Universitas Pelita Harapan, 2024)
Analyze factors influencing consumer interest in Skintific beauty products in the Indonesian market: perceived behavioral control, hedonic value, utilitarian value, and emotional pleasure. A quantitative approach using a Google Form questionnaire was distributed to 324 respondents, focusing on variables like perceived behavioral control, hedonic value, utilitarian value, emotional pleasure,and purchase intention. The study found that hedonic value and perceived behavioral control do not significantly impactpurchase intention. In contrast, utilitarian values and emotional pleasure positively influence purchasing decisions. Notably, perceived behavioral control positively impacts both hedonic and utilitarian values. Additionally, hedonic value positively affects emotional pleasure, emphasizing the importance of experiential enjoyment. However, utilitarian value does not contribute to emotional pleasure, suggesting a potential separation between practical benefits and emotional fulfillment in consumer decision-making. Consumer decisions for Skintific products are more influenced by utilitarian value and emotional pleasure than perceived behavioral control and hedonic value. Insights suggest the importance of control and value perception in shaping consumer behavior in the skincare industry. This information is valuable for marketing and product development strategies.